Engineering antiferromagnetic topological insulators in two-dimensional NaMnBi. Issue 47 (1st November 2021) - Li, Xinying; Mao, Ning; Li, Runhan; Dai, Ying; Huang, Baibiao; Niu, Chengwang
Abstract : Here we predict theoretically that two-dimensional NaMnBi is a promising antiferromagnetic insulator with a topological phase transition via small strain engineering. Abstract : Antiferromagnetic (AFM) topological insulators (TIs) have recently attracted extensive attention as a platform for exploring prominent physical phenomena and innovative design of topological spintronic devices. Here, we theoretically demonstrate a topological switch between the normal insulator and AFM TI in two-dimensional NaMnBi quintuple layers. Using first-principles calculations to systematically investigate the structure, stability, magnetism, and electronic properties, we show that, while the AFM ordering is robust against external strain, the band gap and topology can be effectively tuned. Based on the spin Chern number, Wannier charge centers, and gapless edge states analysis, we identify that the AFM TI phase with out-of-plane magnetization is obtained even under a compressive strain as small as 0.58%. The presented results not only expand our understandings of magnetic topological states but also put forward potential applications in topological AFM spintronics.